Sustainability of Cultural Practices in Ukraine During the War: Challenges and Threats - Nastoiashcha, Kateryna; Marutian, Rena; Sobolevska, Maryna (European Journal of Sustainable Development, 2024)
The article presents the results of the author's All-Ukrainian telephone survey on the topic: "Cultural Practices of the Population of Ukraine during the War". The survey was conducted from June 15 to June 30, 2023 and covered 1,000 adult respondents from all regions of Ukraine, except for the temporarily occupied territories of Crimea and Donbas, as well as areas without Ukrainian mobile communication. The margin of error of the sample does not exceed 2.2%. The article argues that under current conditions, state support for cultural institutions is crucial for Ukraine, and a nationwide strategy for cultural development has become a pressing need. All of this is necessary because only distancing from Russian culture, independence from it, and self-sufficiency are Ukraine's only chance to maintain its agency as a state and preserve its national identity. The stable development of national culture and the formation of a resilient national identity will protect the country from territorial encroachments in the future and help in regaining the occupied territories. Most importantly, they will contribute to the cultural reintegration of the population of these territories, returning them to Ukraine's national cultural space. Keywords: resilience, cultural resilience, sustainable development, war, internally displaced persons (IDPs), respondents, citizens of Ukraine, national values, threats, cultural space